OBJEK-OBJEK DALAM RITUAL PENANGKAL HUJAN - Christy, Imaniar Yordan (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Rain prevention is a ritual that many people do in some areas in Indonesia. In addition to Indonesia, this ritual is also conducted in Japan. The ritual uses various objects. This study discusses the meaning of rain-prevention rituals in some regions of Indonesia and in Japan, and the objects used for the rituals. The purpose of this study is to discover the meaning of rain-prevention rituals, to discover the symbols of ritual objects, and to discover the rainpreventing rituals in some areas in Indonesia and in Japan. The method of analysis used is the method of cultural research